The new consumer: mobile, always connected and social – the user journey perspective - Łysik, Łukasz (Nowy konsument: mobilny, zaangażowany społecznościowo i zawsze online − perspektywa decyzji zakupowych, 2018)
In this article the author provides an analysis of contemporary consumers with a strong emphasis on the rapidly changing business landscape and mobile technologies. The main purpose is to present how modern technology has shaped the consumers, the decisionmaking process and finally their behaviour along the purchase journey. The ICT revolution has once and for all reshaped the business landscape and one of its most visible changes was the rise of the Information Economy and the Mobile Society. The use of mobile technology in today’s economy has caused many changes and a transformation in contemporary business models. The ubiquitous mobile technology has reshaped irrevocably the relationship between entities on the market and created a new type of consumer – the mobile consumer. The purpose of the article is to present this new type of consumers from the perspective of their journey to obtain more information which they needs to include in their purchase decisions
Informatyka Ekonomiczna = Business Informatics, 2018, Nr 4 (50), s. 83-93
Keywords: mobile communication; consumer behaviour; consumer journey; mobile consumer; purchase decisions; technologie mobilne; media społecznościowe; zachowania konsumenckie; mobilny konsument; decyzje zakupowe